Biodistribution and radiodosimetry of a novel myocardial perfusion tracer 123I-CMICE-013 in healthy rats - Duan, Yin; Lockwood, Julia; Wei, Lihui; Hunter, Chad; Soueidan, Karen; Bensimon, Corinne; Fernando, Pasan; Wells, R G; Ruddy, Terrence D (Université d'Ottawa | University of Ottawa, 2014)
Abstract Background 123I-CMICE-013 is a novel radiotracer previously reported to have promising characteristics for single-photon emission computed tomography (SPECT) myocardial perfusion imaging. We evaluated the biokinetics and radiodosimetry of this rotenone-like 123I-labeled tracer in a microSPECT imaging-based study. Methods 37 to 111 MBq of 123I-CMICE-013 was synthesized and administered intravenously to 14 healthy rats. Images were acquired with a microSPECT/CT camera at various time intervals and reconstructed to allow activity quantification in the tissues of interest. Radiation dosage resulted from the injection of 123I-CMICE-013 was estimated base on the biodistribution data. Tissue uptake values from image analysis were verified by gamma-counting dissected organs ex vivo. Results The heart/stomach and heart/intestine uptake ratios peaked shortly after the injection of 123I-CMICE-013, meanwhile the heart/liver ratio reached 2 as early as at 23 min post-injection. Little activity was observed in the lung and overnight clearance was significant in most of the measured tissues. The radiation dosimetry analysis based on the time-activity curves provided an estimate of the effective human dose of 6.99E-03 mSv/MBq using ICRP 60 and 7.15E-03 mSv/MBq using ICRP 103, which is comparable to the popular myocardium perfusion imaging (MPI) agents such as 99mTc-tetrofosmin and 99mTc-sestamibi, as well as other 123I-based radiotracers. Conclusions 123I-CMICE-013 demonstrated desirable characteristics in its biokinetic and radiodosimetric profiles, supporting its potential application as a novel myocardial perfusion imaging agent.